2011
DOI: 10.2298/vsp1110837s
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cronobacter sakazakii from different herbal teas

Abstract: Bacground/Aim. Cronobacter sakazakii (C. sakazakii) is an emerging food-borne pathogen that has increasingly raised interest among the whole public community and food industry, especially in the production of powder infant formula. It has been isolated from water, sediment and soil. The question is whether this pathogen can be present in herbal teas. Herbal teas are widely used for great number of health problems, as an additional or sometimes only “medicine” given. The aim of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…in herbal teas has been reported by a number of researchers (Tamura et al 1995 ;Chap et al 2009 ;Stojanović et al 2011 ). Given the probable plant-based ecosystem for Cronobacter spp.…”
Section: Other Low-moisture Productsmentioning
confidence: 94%
See 1 more Smart Citation
“…in herbal teas has been reported by a number of researchers (Tamura et al 1995 ;Chap et al 2009 ;Stojanović et al 2011 ). Given the probable plant-based ecosystem for Cronobacter spp.…”
Section: Other Low-moisture Productsmentioning
confidence: 94%
“…is not surprising. The largest study reported, to date, was by Stojanović et al ( 2011 ), who isolated C. sakazakii from 48/150 (32 %) of samples. The organism can also persist in prepared tea at 21 and 37 °C.…”
Section: Other Low-moisture Productsmentioning
confidence: 99%
“…Infants, elders, pregnant women, and people who have debilitated immune systems are susceptible populations to foodborne diseases [23]. For example, Cronobacter sakazakii is one of life-threatening bacterium for immunocompromised, low weight individuals and premature infants whose age is less than 28 days [3,[24][25][26][27][28][29]. The infection caused by Cronobacter can be serious for older people and for people whose immune systems are weakened by other illnesses or conditions [30].…”
Section: Vulnerable Age Groupsmentioning
confidence: 99%
“…The Cronobacter genus bacteria were also isolated from tea samples [Maćkiw et al 2011, Turcovský et al 2011. The study conducted by Stojanović et al [2011] showed high prevalence (from 11 to 75%) of C. sakazakii in all kinds of herbal teas, including those intended for infants and children (for example tea from Matricaria recutita).…”
Section: Prevalence Of Cronobacter Spp In Plant-origin Food Productsmentioning
confidence: 99%